A resting place for eternity - Hinz, Daniel; Tharandt, Louise (AAeO - Afrikanistik-Aegyptologie-Online, 2022)
The following paper deals with creating, in an academic context, a digital 3D reconstruction. The individual steps required for a reconstruction based on scientific methods will be presented and explained. The focus is on the source-critical work and the determination of the individual elements to be reconstructed. The technical steps for creating the 3D model will be explained in more detail in accompanying online blog posts. This article aims to show how a modern 3D reconstruction accompanied by proper, source-critical documentation can look like and thus enable a scientific discourse about it.